Identifying the system development issues in managing the electronic medical records system / AP Azli Bunawan - Bunawan, AP Azli (Faculty of Information Management, 2010)
Certain issues need to be considered when purchasing a medical EMR program. The major issues here are objectives and cost for the software. If these issues are not solved, users probably would not purchase it. By defining what is needed first then deciding on the parts that are needed helps determine customers purchasing options. Users should always reserve the right to tell the vendors what they need, not the other way around. This paper also attempt to discuss the solution and recommendation in managing the electronic medical records system.